Economic growth, foreign direct investment and governance oscillation: Empirical evidence from SAARC economies (1996-2015) - NASIR, Maryam; KHAN, Raza Ali; FATIMA, Maham (Journal of Economics Library, 2018)
Abstract. Foreign direct investment (FDI) considered as one of the conventional determinant of Economic growth. Economies that are pursuing for better tomorrow must focus on attracting foreign direct Investments. FDI depends on a number of factors in a country such as market size, level of openness, natural resources, labor cost and productivity, economic growth rate, macroeconomic stability, technology level and so on. Beside these factors, Governance in the recipient economy is also an important pre-determinant of FDI. This study seeks to investigate the impact of FDI (inflows) on Economic growth via Governance through empirical evidence from SAARC economies by using Panel data technique. The data is cross-sectional time series for the period 1996-2015. GDP per capita growth has been used as a variable to assess Economic growth; foreign direct Investment (inflows) and governance data has obtained from World Bank, World Development Indicators. The results indicate that governance does not exert their impact on FDI (inflows) and fails to act as a mediating factor of FDI (inflows) in case of SAARC economies However the SAARC economies should focus on improving level of institutions for catalyzing domestic financial markets. Keywords. Foreign Direct investment (inflows), Governance, Economic Growth, Human Capital, Gross Capital Formation. JEL. F21.